Reflections of the ecological crisis on mental health: a public health-focused review on eco-anxiety and eco-trauma - Çalağan, Canan; Türker, Aylin (The Bulletin of Legal Medicine, 2025)
The deepening ecological crisis in the Anthropocene era poses a significant threat not only to physical but also to mental health. This review aims to examine the reflections of the ecological crisis on mental health through the concepts of eco-anxiety and eco-trauma, from a public health-oriented perspective. Key concepts are defined as eco-anxiety, a chronic state of anxiety about the planet’s future; and eco-trauma, ecological grief, and solastalgia, which emerge as a result of environmental disasters and spatial losses. This review asserts that these psychological responses are not merely individual pathologies but are a collective public health issue deeply connected to environmental injustice and systemic problems. It is stated that the psychosocial burden of the ecological crisis disproportionately affects disadvantaged groups and expands over time to become a societal-level risk. Furthermore, by highlighting the risk of pathologizing the mental health effects of the crisis within existing diagnostic systems, this review emphasizes the need for a holistic solution. In this context, it is concluded that combating the mental health impacts of the ecological crisis is possible not only through individual therapeutic interventions but also through comprehensive public health approaches that include justice, rights-based policies, and the strengthening of social resilience.